Fasilitasi peningkatan kompetensi wirausaha kuliner di era pandemi - Ujang Syahrul Mubarrok; Nuraidya Fajariah; Ahmad Yani (University of Islam Malang, 2021)
The Covid-19 pandemic has an impact on the sustainability of micro, small and medium enterprises, including the businesses of Ngasem residents which have been running so far. Also, businesses owned by residents of Ngasem Village have problems related to entrepreneurial motivation, business management, and limited knowledge about business bookkeeping. The purpose of this service is so that the training participants have a strong motivation to continue doing business, have knowledge of business management, and can manage and make simple business bookkeeping. This method of implementing this service uses lectures, discussions, and cooking practices. During the activity, the participants were very enthusiastic about participating in the training and several participants asked questions. The results of this service activity can increase motivation to continue to work hard, increase the ability of participants to make financial records, and deepen their skills in food processing.